2022
DOI: 10.3390/jcm11175157
|View full text |Cite
|
Sign up to set email alerts
|

Is There Still a Place for Percutaneous Nephrolithotomy in Current Times?

Abstract: Background: Percutaneous nephrolithotomy (PCNL) and its miniaturized modifications are usually considered the standard surgical options for large (>20 mm) staghorn and infected stones. Moreover, PCNL is a viable alternative to retrograde intrarenal surgery (RIRS) for smaller stones (<20 mm) in the presence of anatomical malformations or inaccessible lower pole stones. However, due to the advancements in laser and scope technology, RIRS is expanding its indications with the potential benefits of lower com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 95 publications
0
14
0
3
Order By: Relevance
“…PCNL was first introduced in 1976 ( 9 ). Nowadays, PCNL is the first-line treatment for large and complex renal stones ( 1 , 10 ). However, some patients have residual stones, accounting for 24%–44% of postoperative patients ( 11 ).…”
Section: Discussionmentioning
confidence: 99%
“…PCNL was first introduced in 1976 ( 9 ). Nowadays, PCNL is the first-line treatment for large and complex renal stones ( 1 , 10 ). However, some patients have residual stones, accounting for 24%–44% of postoperative patients ( 11 ).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, RIRS has demonstrated promising results and a review by Breda et al summoned the studies reporting results of RIRS for renal stones >2.5 cm and concluded that an SFR of 89.3% was feasible with an average of 1.6 procedures per case and low complication rate (6). However, comparable results of RIRS to PNL are achievable frequently through staged procedures in high-volume centers, which suggests that RIRS is not yet equivalent to PNL (7). Moreover, technological developments are also contributing to the optimization of PNL procedures, with the miniaturization of the respective scopes and access sheaths, which makes PNL less invasive and safer in terms of complication rate (7).…”
Section: Introductionmentioning
confidence: 99%
“…However, comparable results of RIRS to PNL are achievable frequently through staged procedures in high-volume centers, which suggests that RIRS is not yet equivalent to PNL (7). Moreover, technological developments are also contributing to the optimization of PNL procedures, with the miniaturization of the respective scopes and access sheaths, which makes PNL less invasive and safer in terms of complication rate (7).…”
Section: Introductionmentioning
confidence: 99%
“…1,2 However, minimally invasive approaches might not be appropriate for urolithiasis with anatomical abnormalities and/or a high stone burden because they are technically challenging and have a low stone-free rate. 3 Laparoscopic surgery was one option that some considered. 4 Robotic surgery, however, might be a preferred option due to its superior visualisation and manoeuverability.…”
Section: Introductionmentioning
confidence: 99%